Capital flow management as a tool for ensuring financial stability - V. V. Kuznetsova; O. I. Larina (Вестник университета)
The article relevance is determined by the existing discussions among economists and practitioners about the advantages, disadvantages and consequences of the use of control over the cross-border movement of capital. The subject of the article is the study of the permissibility of the systematic use of capital control measures (“Capital Control”, control over cross-border capital movement, including restrictions on cross-border transactions; a complete or partial ban on currency exchange operations; introduction of restrictions on foreign investments in national assets or on national investments in foreign assets, etc.) to maintain the stability of the national financial system. The purpose of the article is to analyze opinions and factual data on the application of measures to control the cross-border movement of capital, systematization of the possible consequences of this tool for Russia. Based on the analysis of empirical data, country analysis and documents of the International Monetary Fund, the authors have compiled a classification of capital control measures, identified their main groups, identified the reasons for their use, and systematized the advantages and disadvantages of using such measures. The authors conclude that depending on the motives of the regulator, there may be different approaches to the application of capital control measures. The use of the results of this study may be useful for regulators of the Russian financial market, since capital control measures are in force in Russia.